Resolution of SPAM following cordectomy: implications for understanding pathophysiology. - Meagher, T; Belci, M; López de Heredia, L; Ansorge, O; Jamous, A; Saif, M; Hughes, R (2012)
STUDY DESIGN: Case report. OBJECTIVE: To describe the clinical benefit of a spinal cordectomy with the aim of limiting neurological deterioration related to the development of a subacute posttraumatic ascending myelopathy (SPAM) supporting previously described mechanism for SPAM formation. SETTING: National Spinal Injuries Centre, Stoke Mandeville Hospital, UK. METHOD AND RESULTS: A 38-year old patient presented 6 months after spinal cord injury substantial neurological deterioration expanding from the initial T4-injury level through C4. Magnetic resonance imaging revealed intra-medullary haemorrhage at the site of injury and subsequent-ascending cord oedema. A cordectomy was performed leading to neurological stabilisation and complete resolution of SPAM. CONCLUSION: Cordectomy can be an effective intervention in case of rapid progressive neurological deterioration.